Autosomal and X chromosome structural variants are associated with congenital heart defects in Turner syndrome: The NHLBI GenTAC registry. Issue 12 (8th September 2016) - Prakash, Siddharth K.; Bondy, Carolyn A.; Maslen, Cheryl L.; Silberbach, Michael; Lin, Angela E.; Perrone, Laura; Limongelli, Giuseppe; Michelena, Hector I.; Bossone, Eduardo; Citro, Rodolfo; Lemaire, Scott A.; et al.
Abstract : Turner Syndrome (TS) is a developmental disorder caused by partial or complete loss of one sex chromosome. Bicuspid aortic valve and other left‐sided congenital heart lesions (LSL), including thoracic aortic aneurysms and acute aortic dissections, are 30–50 times more frequent in TS than in the general population. In 454 TS subjects, we found that LSL are significantly associated with reduced dosage of Xp genes and increased dosage of Xq genes. We also showed that genome‐wide copy number variation is increased in TS and identify a common copy number variant (CNV) in chromosome 12p13.31 that is associated with LSL with an odds ratio of 3.7. This CNV contains three protein‐coding genes ( SLC2A3, SLC2A14, and NANOGP1 ) and was previously implicated in congenital heart defects in the 22q11 deletion syndrome. In addition, we identified a subset of rare and recurrent CNVs that are also enriched in non‐syndromic BAV cases. These observations support our hypothesis that X chromosome and autosomal variants affecting cardiac developmental genes may interact to cause the increased prevalence of LSL in TS. © 2016 Wiley Periodicals, Inc.